Issue Thérapeutique Des Patients Tuberculeux Pulmonaires Biologiquement Confirmés Dans La Zone Sanitaire De Parakou-N’Dali De 2011 À 2015 - Dovonou, CA; Alassani, CA; Ade, S; Attinsounon, CA; Ahoui, S; Tognon, FT; Zannou, DM; Ade, G; Houngbe, F (European Scientific Journal, ESJ, 2016)
Objective: The objective of this study is to describe the therapeutic outcome and factors associated with treatment failure in laboratory confirmed pulmonary tuberculosis patients. Methods: He acted in a descriptive and analytical study referred to prospective data collection. The study population consisted of laboratory confirmed pulmonary tuberculosis patients in the health zone Parakou-N’Dali from 2011 to 2015. Results: A total of 313 TB patients were enrolled. The average age of patients was 37.4 ± 14.3 years. The sex ratio was 2.1. Two hundred sixtyfive (265) patients were cured, a cure rate of 84.66%; 5 patients had completed treatment. Therapeutic success was observed in 270 patients (86.26%); the rate of treatment failure was 2.24%. Twenty-nine (29) patients died (9.26%); 6 patients were lost to follow and only 1 was transferred. Factors associated with treatment failure were the BMI screening to the lower than 18.5 kg/m2 (p = 0.000) and hospitalization (p = 0.002).Conclusion: The therapeutic outcome of patients with pulmonary tuberculosis in the health zone Parakou-N’Dali was characterized by a low rate process complete, lost sight and transfers.